Behavioural risk factors in adults with chronic diseases in Spain (Boletín Epidemiológico Semanal, 2025)
Introduction: To describe the prevalence of the main modifiable risk factors in adults with chronic diseases in Spain.Method: Data come from 67,451 individuals aged ≥15 years participating in the National Health Survey 2017 and European Health Surveys 2014 and 2020. Prevalences of tobacco use, alcohol consumption, fruit and vegetable consumption, and leisure-time physical activity were estimated in individuals with a history of myocardial infarction (n=1,530), stroke (n=1,382), diabetes (n=6,309), chronic obstructive pulmonary disease (COPD, n=2,831), asthma (n=3,078), and cancer (n=3,086).Results: Current tobacco use ranged from 22.5% in people with COPD to 13.4% with a history of heart attack. The highest prevalence of high-risk drinking was observed in the population with asthma and COPD (11.6% and 11.5%), and the lowest in people with stroke (5.9%). Consumption
Keywords: chronic diseases; tobacco; alcohol; diet; sedentarism; secundary and tertiary prevention